Effect of sulphur hexafluoride (SF6) plasma on hydrophobicity of methylcellulose film - Rachtanapun P. (2014)
Effect of plasma treatments (power, pressure and treatment time) on hydrophobicity (contact angle and water absorption time) and sorption isotherm of methylcellulose (MC) film using sulphur hexafluoride (SF6) were investigated. MC film specimens were precondition in desiccators containing silica gel at 25 ±2°C for 48 h. MC film specimens were plasma treated by an inductivity coupled plasma discharged (ICP) at 13.56 MHz with operating powers (25-75 W) and gas pressures (20-200 mTorr). The treatment times (10-300 second). Hydrophobicity of treated methylcellulose film outstandingly increased. The best plasma treatment condition was power 50 W and 100 mTorr. The treated MC film had higher contact angle and water absorption time than untreated sample at all operated treatment times; contact angle was increased up to 56-80°. These results were corresponding to sorption isotherm. The treated film was absorbed moisture higher than untreated film. © (2010) Trans Tech Publications.